2021
DOI: 10.1111/tri.14131
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering transplant outcomes of expanded kidney allografts donated after controlled circulatory death in the current transplant era. A call for caution

Abstract: Outcomes of kidney transplantation (KT) after controlled circulatory death (cDCD) with highly expanded criteria donors (ECD) and recipients have not been thoroughly evaluated. We analyzed in a multicenter cohort of 1161 consecutive KT, granular baseline donor and recipient factors predicting transplant outcomes, selected by bootstrapping and Cox proportional hazards, and were validated in a contemporaneous European KT cohort (n = 1585). 74.3% were DBD and 25.7% cDCD-KT. ECD-KT showed the poorest graft survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Successful utilization and transplantation of marginal organs relies on appropriate donor-recipient matching. Multiple studies have showed an overall survival benefit from transplantation with “marginal” donors compared to remaining waitlisted for nearly all candidates [ 32 , 33 , 34 ]. The results of the present study emphasize the need to maximize kidney utilization from NID, considering that the donor population is growing increasingly older, more obese, and has a higher prevalence of comorbid conditions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Successful utilization and transplantation of marginal organs relies on appropriate donor-recipient matching. Multiple studies have showed an overall survival benefit from transplantation with “marginal” donors compared to remaining waitlisted for nearly all candidates [ 32 , 33 , 34 ]. The results of the present study emphasize the need to maximize kidney utilization from NID, considering that the donor population is growing increasingly older, more obese, and has a higher prevalence of comorbid conditions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplants from donors who are elderly, ECD, ECD/DCD, or kidneys with pre-existing lesions have poorer prognoses than transplants from standard-criteria donors. Recipients of organs from high-risk donors tend to have poor renal function, with reduced medium-term graft survival ( 12 , 13 ). Such patients are also at high risk of delayed graft function (DGF) ( 14 , 15 ).…”
Section: Immunogenicity Of Kidney Graft Depends On Donor Characteristicsmentioning
confidence: 99%
“…Across a number of studies, ECD-DCD kidneys report acceptable 3-year death-censored graft survival rates between 70%–90%, which are inferior to SCD-DCD kidneys but not ECD-DBD kidneys ( 26 - 32 ). However, Montero et al demonstrate how important selecting the most appropriate donor-recipient combination is in a recently published risk modelling study ( 33 ). In their multi-center cohort study, mortality risk for the highest risk-stratification group receiving ECD-DCD kidneys was significant.…”
Section: Donor Clinical Factorsmentioning
confidence: 99%